High Prevalence of Hepatitis B Among Secondary School Students: Implications for Vaccination Programs and Public Health (JURNAL PROTEKSI KESEHATAN, 2025)
This cross-sectional study, conducted in five secondary schools in White Nile State, Central Sudan, aims to assess the seroprevalence of Hepatitis B Virus (HBV) among students aged 14-20 years. Utilizing a sample of 384 students, the study employs the Enzyme-Linked Immunosorbent Assay (ELISA) technique to detect HBV surface antigens (HBsAg). The results reveal a high prevalence rate of 49%, with significant correlations between HBV infection and factors such as gender, marital status, blood transfusion history, family history of HBV, and vaccination status. Notably, female students exhibit a higher prevalence rate (55%) compared to male students (45%). Married students show a 100% prevalence rate, indicating a strong link between marital status and HBV infection. Additionally, students with a history of blood transfusions and those with family histories of HBV are more likely to be infected. Vaccination history emerges as a critical factor, with vaccinated students displaying lower infection rates, underscoring the importance of vaccination programs. These findings emphasize the need for enhanced HBV awareness, regular screening, and vaccination campaigns to mitigate the virus's spread among young populations in similar settings, ultimately contributing to better public health outcomes